2000
DOI: 10.1017/s0261444800015688
|View full text |Cite
|
Sign up to set email alerts
|

Issues of language and gender in second and foreign language education

Abstract: She teaches 'Gender and language', as well as other undergraduate and postgraduate courses, and is the Director of Studies of the new 'PhD in Applied Linguistics byTltcsis and CourscworW programme. Her main research interest is gender and language, both inside and outside the classroom, and she is currently looking at different ways of researching language and gender in literature written for young children. She is also working on a research project concerned with how doctoral students become members of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 140 publications
3
69
2
2
Order By: Relevance
“…However, the results appear to be in contrast to a view that has almost become general: the assumption that female students are in general more successful in language learning than their male counterparts (Sunderland, 2000).…”
Section: Discussion Theory and Practice In Language Studies 1873contrasting
confidence: 99%
“…However, the results appear to be in contrast to a view that has almost become general: the assumption that female students are in general more successful in language learning than their male counterparts (Sunderland, 2000).…”
Section: Discussion Theory and Practice In Language Studies 1873contrasting
confidence: 99%
“…In providing such support, however, the results appear to be in contrast to a view that has become almost commonsensical: the assumption that female students are in general more successful in language learning than their male counterparts (Sunderland, 2000). Based on the result of Progress International Reading Literacy Study (PIRLS, 2006) as reported by Arellano (2013), female students have a higher achievement in literal reading in all European countries.…”
Section: Part IImentioning
confidence: 59%
“…Producing vocabulary is a more demanding task than receiving it and the former could be more closely connected to motivation as a desire of wanting to transmit a message is necessarily required in production but not in reception . Differences in the results are not only suggested for productive and receptive tasks, but also for different types of productive tasks and different types of receptive tasks (Jiménez Catalán and Ojeda Alba, 2009;Sunderland 2000). For instance, boys have been found to be superior in multiple-choice tasks and girls in extended writing tasks (Sunderland, 2000: 212-213) .…”
Section: Rq 2 Gender Variation In Types Of Motivation Towards the Fmentioning
confidence: 91%